2020
DOI: 10.1002/hipo.23292
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions preserve hippocampal volume: A meta‐analysis

Abstract: Hippocampal volume is a marker of brain health and is reduced with aging and neurological disease. Exercise may be effective at increasing and preserving hippocampal volume, potentially serving as a treatment for conditions associated with hippocampal atrophy (e.g., dementia). This meta‐analysis aimed to identify whether exercise training has a positive effect on hippocampal volume and how population characteristics and exercise parameters moderate this effect. Studies met the following criteria: (a) controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 83 publications
5
48
1
Order By: Relevance
“…When examining the characteristics of the samples and interventions, the overall effect was significant for adults 65 years and older, interventions 24 weeks or longer, and interventions providing up to 150 min of exercise per week (Wilckens et al, 2021). These findings suggest that the parameters of the intervention and sample characteristics may account for some of the heterogeneity in findings across the field.…”
Section: Hippocampal Morphologymentioning
confidence: 82%
See 3 more Smart Citations
“…When examining the characteristics of the samples and interventions, the overall effect was significant for adults 65 years and older, interventions 24 weeks or longer, and interventions providing up to 150 min of exercise per week (Wilckens et al, 2021). These findings suggest that the parameters of the intervention and sample characteristics may account for some of the heterogeneity in findings across the field.…”
Section: Hippocampal Morphologymentioning
confidence: 82%
“…However, one of these studies reported an exercise adherence rate of only 36% (Krogh et al, 2014), raising methodological and theoretical questions about the inclusion of studies with both poor and good (>80%) adherence rates. A recent meta-analysis of exercise interventions found a significant reduction in control groups' total hippocampal volume from pre-to post-intervention, but not left or right hippocampal volume, while an overall increase in the intervention group was not significant (Wilckens et al, 2021).…”
Section: Hippocampal Morphologymentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, increased default mode network (DMN) activity is associated with poorer inhibitory control ( Congdon et al, 2010 ), thus physical training’s decrease of DMN may have an indirect benefit on inhibitory control mechanisms ( Boraxbekk, Salami, Wåhlin & Nyberg, 2016 ; Li et al, 2017 ). Additionally, physical training literature has demonstrated structural and functional physical training induced benefits for memory ( Wanner, Cheng & Steib, 2020 ; Wilckens et al, 2020 ) and higher-level executive functions such as inhibition control ( Verburgh, Königs, Scherder & Oosterlaan, 2014 ; Xue, Yang & Huang, 2019 ). For example, regular physical training is associated with increased grey matter volume in the prefrontal cortices ( Erickson, Leckie, & Weinstein, 2014 ; Den Ouden et al, 2018 ), which support a range of executive functions including inhibitory control ( Aron, Robbins & Poldrack, 2014 ; Bari & Robins, 2013 ; Bird & Burgess, 2008 ; Kim, Choi & Chung, 2016 ; Kim & Sung, 2017 ; Park & Kim, 2017 ; Swick, Ashley & Turken, 2011 .…”
Section: Introductionmentioning
confidence: 99%